STRATEGI PENGEMBANGAN OBJEK WISATA ALAM KAMPUNG PASUNDAN CISAMAYA DI DESA PASAWAHAN KABUPATEN KUNINGAN - Rizal Rusdianto; Ilham Adhya; Yayan Hendrayana (Journal of Forestry And Environment, 2023)
This study aims to determine the potential and development strategies of the Natural Tourism Object of Pasundan Cisamaya Village, because there has been no previous research. Database collection techniques are carried out by means of tourism potential, tourism demand potential, survey methods, documentation methods and literature studies. The data analysis technique uses quantitative descriptive analysis techniques.The strategy for developing the Natural Tourism Object in Pasundan Cisamaya Village is formulated through a SWOT analysis which includes internal factors, namely there are 5 strengths and 4 weaknesses as well as external factors there are 4 opportunities and 2 threats resulting from direct observations in the field and interviews with the managers of the Natural Tourism Objects of Pasundan Cisamaya Village.Based on the internal and external factors of the Pasundan Cisamaya Village Nature Tourism Object, the most appropriate strategy to use is the SO (Strengths Opportunity) strategy, SO strategies that can be used are: 1) Increasing cooperation with community groups. 2) Utilization of traditional dances as educational tours. 3) Opening up business opportunities for the surrounding community. 4) Developing all the potential that is owned, working together between managers, communities and visitors Keyword: Pasundan Village Cisamaya, Potency, Development Strategy.Penelitian ini bertujuan untuk mengetahui potensi dan strategi pengembangan Objek Wisata Alam Kampung Pasundan Cisamaya, karena belum ada penelitian sebelumnya. Teknik pengumpulan data dilakukan dengan cara wawancara, observasi dan studi literatur. Teknik analisis data menggunakan teknis analisis deskriptif kuantitatif. Data hasil penelitian yang telah dikumpulkan terkait dengan kondisi fisik, kondisi sosial, sarana dan prasarana, faktor pendukung, faktor penghambat, dan potensi yang ada, Strategi pengembangan Objek Wisata Alam Kampung Pasundan  Cisamaya  dirumuskan  melalui  analisis  SWOT  yang  meliputi  faktor  internal  yaitu terdapat 5 kekuatan dan 4 kelemahan serta faktor eksternal terdapat 4 peluang dan 2 ancaman yang dihasilkan dari pengamatan langsung dilapangan serta wawancara kepada pengelola Objek Wisata Alam Kampung Pasundan Cisamaya. Berdasarkan faktor internal dan eksternal Obyek Wisata Alam Kampung Pasundan Cisamaya strategi yang paling tepat untuk digunakan adalah strategi SO (Strengths Opportunity), Strategi SO yang dapat digunakan yaitu :   1) Meningkatkan kerjasama dengan  kelompok  masyarakat.  2)  Pemanfaatan tari  tradisional sebagai  wisata  pendidikan.  3) Membuka  peluang  usaha  bagi  masyarakat  sekitar.  4)  Mengembangkan  semua  potensi  yang dimiliki, bekerjasama antar pihak pengelola, masyarakat dan pengunjung